Advanced Metastatic Bilateral Breast Carcinoma in a Pregnant Woman With HIV During the Second Trimester: A Rare Case Report and Review of the Current Literature - John Lugata; Laetitia Makower; Christiane Niyoyitungira; Praygod Kitiwi; Tecla Lyamuya; Eusebious Maro; Bariki Mchome; Alex Mremi (Clinical Case Reports)
ABSTRACT Breast cancer is the most common cancer among women worldwide and the leading malignancy diagnosed during pregnancy. The estimated incidence of breast cancer in pregnancy is 6.5 cases per 100,000 live births. Management during pregnancy is guided by gestational age, aiming to achieve a safe full‐term delivery while minimizing adverse effects on the mother's prognosis. While the goal is to provide treatment comparable to that of nonpregnant patients, standard therapies must be adapted to ensure the safety of both the mother and the fetus. Herein we present the case of a 29‐year‐old, G3P2L2 woman in Northern Tanzania. Our patient presented at 20 weeks with a 5‐month history of bilateral breast masses and a 2‐month history of back pain and lower limb weakness. The masses had developed gradually after conception and grew over time. Her breasts had been normal during her two previous pregnancies. Past medical history was notable for a new diagnosis of HIV/AIDS which was being treated with Abacavir (ABC), Lamivudine (3TC), and Dolutegravir (DTG). A contrast CT scan of the head and neck revealed diffuse expansible lytic lesions involving skull bones, cervical spine, exposed upper ribs, and scapulae. Right axillary lymph node enlargement was also seen. A core needle biopsy was taken from both breasts, and the final histopathological report revealed an infiltrating ductal carcinoma, NST, Grade 2. After discussion by the tumor board, the decision was made to proceed with palliative management and close follow‐up. Unfortunately, she passed away 1 week later due to respiratory complications.